The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
The 8th Electrical Engineering/ Electronics, Computer, Telecommunications and Information Technology (ECTI) Association of Thai 2011
DOI: 10.1109/ecticon.2011.5947987
|View full text |Cite
|
Sign up to set email alerts
|

Reserve margin evaluation for generation system using probabilistic based method

Abstract: Reserve margin is one of the generation system reliability indices which should be appropriately defined. Too high reserve margin causes over-investment in generation system whereas too low reserve margin may result in unacceptable generation risk. This paper proposes method to calculate the value of appropriate reserve margin based on probabilistic method using a reliability index, i.e. Loss of Load Expectation (LOLE). Three generic capacities, i.e. 250, 500, and 750 MW, are used and tested with a modified Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Ang'u et al (2020) analyze the role of reserve margin in electricity tariffs in Kenya using a regression model and it is shown that the reserve margin has a role in determining the electricity prices. Diewvilai et al (2011) propose a probabilistic approach to determine the appropriate reserve margin for an electrical system taking Thailand as the case study. Their main motivation is that too much reserve margin requires over-investment in generation capacity whereas too low a margin might cause generation risk and decreased reliability.…”
Section: Background and Literature Reviewmentioning
confidence: 99%
“…Ang'u et al (2020) analyze the role of reserve margin in electricity tariffs in Kenya using a regression model and it is shown that the reserve margin has a role in determining the electricity prices. Diewvilai et al (2011) propose a probabilistic approach to determine the appropriate reserve margin for an electrical system taking Thailand as the case study. Their main motivation is that too much reserve margin requires over-investment in generation capacity whereas too low a margin might cause generation risk and decreased reliability.…”
Section: Background and Literature Reviewmentioning
confidence: 99%
“…High Reserve Margin can provide high reliability to the system. However, it acquires more generation plant, for which some of them may not be necessary [1]. This can cause over investment in generating capacity that can lead to excessive operating costs which may be reflected in the tariff structure [2].…”
Section: Introductionmentioning
confidence: 99%
“…There are many studies involves in determining the generation reliability such as LOLE. Study of [1] proposed method to determine appropriate Reserve Margin by using probabilistic base method. The method is to calculate the value of appropriate Reserve Margin based on probabilistic method using a reliability index, i.e.…”
Section: Introductionmentioning
confidence: 99%